2020
DOI: 10.1007/s10096-020-04049-6
|View full text |Cite
|
Sign up to set email alerts
|

The vaginal microbiota in the course of bacterial vaginosis treatment

Abstract: Bacterial vaginosis (BV) is perceived as a condition of disrupted vaginal microbiota, but remains of unknown aetiology. In this study, vaginal microbiota composition was determined in twenty-one women with BV, before and after treatment with metronidazole or clindamycin. Microbiota composition varied greatly between women and defining a (un)healthy vaginal microbiota state remains elusive, challenging BV diagnosis and treatment. While relative abundance of Lactobacillus increased after antibiotic treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Several studies have indicated that bacterial vaginosis is associated with infertility [11]. Bacterial vaginosis has also been shown to alter the vaginal microbiome [12]. A previous study demonstrated that the vaginal microbiome plays an important role in the pathophysiology of primary ovarian failure, and the relative abundance of bacteria in the genus Lactobacillus was significantly lower in women with primary ovarian failure than in healthy controls [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that bacterial vaginosis is associated with infertility [11]. Bacterial vaginosis has also been shown to alter the vaginal microbiome [12]. A previous study demonstrated that the vaginal microbiome plays an important role in the pathophysiology of primary ovarian failure, and the relative abundance of bacteria in the genus Lactobacillus was significantly lower in women with primary ovarian failure than in healthy controls [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that the current definition of BV, based on microscopy, is inadequate and will need revision as further genomic based studies improve our understanding of the condition. 27 Our study has a number of limitations. The study population was limited to women with recurrent and symptomatic BV and participants were mostly sexual health attendees, therefore our findings may not be generalisable to asymptomatic women or women with less severe BV.…”
Section: Discussionmentioning
confidence: 93%
“…In the event of confirmed anaerobes, the next step is usually antibiotic therapy with metronidazole (oral or vaginal) or clindamycin (oral or vaginal) [ 77 ]. One reason for the high rate of re-infection is the different spectrums of activity of metronidazole and clindamycin: Gardnerella vaginalis and Atopobium vaginae are sensitive to clindamycin, but the simultaneous activity of clindamycin against lactobacilli is disadvantageous.…”
Section: Antibioticsmentioning
confidence: 99%